Investigation of the ground effects of Mw7.8 and Mw7.5 Maraş doublet earthquake on the south-east region (Bİtlİs-Zagros fold-thrust belt) of Turkey - Pirti, Atinc (INST GEOLOGY & GEOGRAPHY, 2024)
The Bitlis-Zagros Fold -Thrust Belt is one of the world's largest deformation zones, extending from the Eastern Mediterranean in southern Turkey to the south of Iran. This deformation zone is partitioned between different structures; however, little is known about the relative activities of these different structures and their effects on topography. The aim of this paper is to investigate the coseismic displacements resulting from the doublet earthquake that occurred in the vicinity of the city of Mara & scedil; (6 February 2023) by utilizing GNSS (Global Navigation Satellite System) stations (near the Bitlis-Zagros Fold -Thrust Belt) that are part of the CORS-TR (Continuously Operating Reference Station-T & uuml;rkiye) geodetic network. After the doublet Mara & scedil; earthquake, south-westerly movements were observed at the ELAZ station, and south-east movements were observed at ERGN and MARD stations. As can be seen from the data obtained from these CORS-TR stations, the effect of the earthquake on the horizontal and vertical components was approximately 0.2-7.2 cm. These motions of ELAZ, ERGN and MARD stations can cause other earthquakes in the region of Bing & ouml;l, Van, Bitlis and Mu & scedil; in the future.
Keywords: Mara$ Earthquakes 2023; displacement; deformation; accuracy; precision; EVOLUTION; TECTONICS; Geology